Thirty years after the fall of the Berlin wall in Germany and celebration - Majumdar, Ananda (American Journal of Economics and Business Management, 2019)
Germany is one of the most developed nation state in the world order. It is celebrating its 30 years of the fall of the Berlin Wall on 4th to 10th November, 2019. It is a great country, great Germans. The preparation of the celebration is in full swing. Germany is ready to welcome people from all over the world to participate this mega event. However the domestic equality in economy, social between former East and West Germany is still different on the eve of 30 years of celebration. They are different in their dialect pronunciation, they different in economy, life standard and households development. This is not expected from such as strong and vast art and culture focused country and from a strong German nation. The objective of the paper is to share its upcoming celebration on the fall of Berlin Wall which is really a global event and discuss its domestic inequality since its reunification (1989) to at present. The outcome of the paper is to understand Germany’s pros and cons socially, economically, politically and its reasons behind and also to gain a knowledge about Germany through its in-depth discussion in the context of the great Berlin Wall. The outcome of the research exists on community sharing and thus learning about Germany among the new generation. The feature question of this research paper is; Germany is one of the G8, the most industrialized country in the world, why a part of Germany is underdeveloped compare to it’s another part even its extreme status in the world order from its history to the present?